Super dog Supplementary reading material - Roderick Hunt (Oxford Reading Tree, 2012)
The Level 9 Biff, Chip and Kipper Stories, written by Roderick Hunt and illustrated by Alex Brychta, provide a rich story context to help develop language comprehension and decoding skills. Stories and More Stories A continue to $1! =s